Analisis Terhadap Yayasan Lembaga Bantuan Hukum Pekanbaru dalam Pemberian Bantuan Hukum - Samariadi, Samariadi; Riznawara, Ihsan; Ramadhani, Fitria Laila; Putri, Shintia Novariani; Imanuela, Sonya Maduma; Apsalina, Phalosa Dwi (Universitas Pahlawan Tuanku Tambusai, 2024)
Legal aid is a legal service provided by legal aid providers free of charge to legal aid recipients. Providing legal aid is one way to achieve justice, especially for poor people. Legal aid has also been regulated in Indonesian legislation, namely in Law Number 15 of 2011 concerning Legal Aid. The provision of legal aid has been carried out by legal aid providers. A legal aid institution is an institution that is run to provide legal assistance. Law Number 16 of 2011 is basis for legal aid institutions in carrying out their duties. In this case, legal aid institutions provide legal assistance both in litigation and non-litigation. People always think that it is difficult to resolve legal issues due to several factors. One of these factors is the large costs that will be incurred. For this reason, legal aid is present in society to realize justice in obtaining equal rights under the law. Legal aid institutions exist as a manifestation of the state's obligation to protect and recognize the human rights of every citizen. Legal Aid Institutions have become more widespread. One of the Legal Aid Institutions is YLBHI-LBH Pekanbaru. This Legal Aid Institute has resolved many cases both in litigation and non-litigation.